Gain-of-function gene mutations and venous thromboembolism: distinct roles in different clinical settings. Issue 6 (16th February 2007) - Colaizzo, Donatella; Amitrano, Lucio; Iannaccone, Luigi; Vergura, Patrizia; Cappucci, Filomena; Grandone, Elvira; Guardascione, Maria Anna; Margaglione, Maurizio
Abstract : Objective: To calculate the prevalence of common gain of function gene mutations in patients with different clinical manifestations of venous thromboembolism. Design and setting: Case–control study in two hospitals in Italy. Participants: 387 patients with venous thromboembolism and 286 controls. Main measures: Factor V (FV) Leiden, factor II (FII) A20210 and JAK2 V617F mutations. Results: Among patients with deep vein thrombosis in one leg, 23 (20.9%) carried FV Leiden and FII A20210 mutations. Similar figures were observed in patients with cerebral vein thrombosis (CVT; n = 9; 20.0%) and in patients presenting with splanchnic vein thrombosis (SVT; n = 26; 18.7%). A lower prevalence was obtained in patients with retinal vein thrombosis (n = 11; 11.8%). The JAK2 F617 mutant allele was found in 27 (21.1%) patients with SVT, but in none of the patients presenting with a thrombotic event from different districts. 13 of the 27 JAK2 V617F-positive subjects with SVT were previously known to have a myeloproliferative disease (MPD). Three other patients had a diagnosis of MPD after the occurrence of the thrombotic event. Conclusion: Carriership of FV Leiden or FII A20210 mutations identifies an at-risk condition for venous thrombosis in the lower extremities, SVT or CVT. In patients with SVT, screening for the JAK2 V617F mutation may be useful in recognising patients who should be carefully observed for the subsequent development of overt MPD. Thus, genetic tests may play a different role, various clinical manifestations of venous thromboembolism being associated with distinct risk profiles.